An equation of a curve can also represent a pair of straight lines. If x 2 − 4 x y + 4 y 2 + x − 2 y − 6 = 0 represents a pair of parallel lines. Then find out the distance between them.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 2 − 4 x y + 4 y 2 + x − 2 y − 6 = 0 represents 2 parallel lines. So we can write the equation as:
( x − 2 y + c 1 ) ( x − 2 y + c 2 ) because they are parallel the coeffient of x and y are the same and when we simplify we get:
x 2 − 4 x y + 4 y 2 + ( c 1 + c 2 ) x − 2 ( c 1 + c 2 ) y − c 1 ⋅ c 2 = 0
∴ c 1 + c 2 = 1 and c 1 ⋅ c 2 = − 6
⇒ c 1 = 3 and c 2 = − 2 OR ⇒ c 2 = 3 and c 1 = − 2
∴ distance = ∣ ∣ ∣ ∣ ( 1 ) 2 + ( − 2 ) 2 c 1 − c 2 ∣ ∣ ∣ ∣ = 5 ,where 1 and − 2 are coeffients of x and y .
Problem Loading...
Note Loading...
Set Loading...
Given that x 2 − 4 x y + 4 y 2 + x − 2 y − 6 = 0 represents a pair of parallel lines, we can find the \two y - and x -intercepts by putting x = 0 and y = 0 respectively, we have:
⎩ ⎨ ⎧ x = 0 y = 0 ⟹ 4 y 2 − 2 y − 6 = 0 ⟹ x 2 + x − 6 = 0 ⟹ 2 ( y + 1 ) ( 2 y − 3 ) = 0 ⟹ ( x + 3 ) ( x − 2 ) = 0 ⟹ y = − 1 , 2 3 ⟹ x = − 3 , 2
From the four intercepts we note that the two parallel lines are { 2 y = x + 3 2 y = x − 2 as shown in the figure. Also note that ( x + 3 − 2 y ) ( x − 2 − 2 y ) = x 2 − 4 x y + 4 y 2 + x − 2 y − 6 .
Let us drop a perpendicular from y -intercept A ( 0 , 2 3 ) to the line 2 y = x − 1 at point C . Then A C is the distance between the two parallel lines. Since the gradient of the parallel lines is 2 1 , then ∠ B A C = tan − 1 2 1 , where B ( 0 , − 1 ) is the other y -intercept. We note that A C = A B cos ∠ B A C = 2 5 × 5 2 = 5 .